Features of adaptive immunity in children with moderate acute urticaria - S. V. Maltsev; L. P. Sizyakina; A. A. Lebedenko (Медицинский вестник Юга России, 2019)
Objective: to study the state of adaptive immunity in children with moderate acute urticaria.Materials and methods: 139 children with moderate acute urticaria were examined. Clinical methods included analysis of anamnestic data, objective examination of the child. Immunological methods of investigation included determination of t-lymphocyte, B-lymphocyte populations by fl ow cytofl uorometry, circulating immune complexes by spectroturbidimetry, determination of secretory IgA, IgA, IgM, IgG, IL-4, IL-6, IL-17 by enzyme immunoassay of blood serum.Results: the analysis of adaptive immunity parameters in children with moderate acute urticaria revealed activation of humoral immunity, reduction of early activation and apoptotic readiness of lymphocytes, reduction of secretory IgA, increase in circulating immune complexes, high levels of IL-17.Conclusion: the revealed changes indicate an imbalance in the functioning of the adaptive link of the immune system, activation of the cytokine cascade of infl ammation, which is accompanied by further activation of the regulatory components of the infl ammatory process